The role of in vitro testing in pharmacovigilance for ß-lactam-induced serum sickness-like reaction: A pilot study - Elzagallaai, Abdelbaset A.; Abuzgaia, Awatif M.; Del Pozzo-Magaña, Blanca R.; Loubani, Eman; Rieder, Michael J. (Frontiers in Pharmacology, 2022)
Background: Current pharmacovigilance (PV) methods for detection of adverse drug reactions (ADRs) fail to capture rare idiosyncratic reactions due to their scarcity and the lack of clear diagnostic criteria. Drug-induced serum sickness-like reactions (SSLRs) are rare idiosyncratic drug-induced hypersensitivity reactions that occur in susceptible patients 1-3 weeks after exposure to the culprit drug with ß-lactam antibiotics being the most associated drugs. The diagnosis of drug induced SSLR is difficult due to the lack of safe and reliable diagnostic tests for identifying the culprit drug. The lymphocyte toxicity assay (LTA) is an in vitro test used as a diagnostic tool for drug hypersensitivity reactions (DHRs). Objective: To evaluate the role of the LTA test for diagnosing and capturing SSLR due to ß-lactam antibiotics in a cohort of patients. Methods: Patients were recruited from patients referred to the Drug Hypersensitivity Clinic at Clinic at London Health Science Centre with suspicion of drug allergy. Twenty patients (10 males and 10 females) were selected to be tested to confirm diagnosis. Demographic data was collected form the patents and blood samples were withdrawn from all patients and from 20 healthy controls. The LTA test was performed on all subjects and data is expressed as percentage increase in cell death compared to control (vehicle without the drug). Results: In the result of LTA tests performed on samples from the selected 20 patients. There was a significant (p<0.05) concentration-dependent increase in cell death in cells isolated from patients as compared to cells from healthy controls when incubated with the drug in the presence of phenobarbitone-induced rat liver microsomes. Conclusion: Giving its safety and good predictive value the LTA test has very strong potential to be a useful diagnostic tool for ß-lactam-induced SSLR. The test procedure is relatively simple and not overly costly. Further studies including other drug classes are needed to evaluate the utility of the LTA test for SSLR due to other drugs.